A homeotropic main-chain tolane-type liquid crystal elastomer film exhibiting high anisotropic thermal conductivity. Issue 32 (20th July 2017) - Ge, Si-Jia; Zhao, Ti-Peng; Wang, Meng; Deng, Lin-Lin; Lin, Bao-Ping; Zhang, Xue-Qin; Sun, Ying; Yang, Hong; Chen, Er-Qiang
Abstract : Homeotropic aligned main-chain tolane-type liquid crystal elastomer films with high normal-to-plane thermal conductivity and high thermal conductivity anisotropy are described. Abstract : The development of pure polymeric films with anisotropic thermal conductivities for electronic device packaging applications has attracted intense scientific attention. In order to enhance the polymeric film's normal-direction thermal conductivity, homeotropic alignment of macromolecular chains is the primary concern. One of the promising preparation strategies is to perform in situ photopolymerization of homeotropic-oriented liquid crystal monomers. In this work, we design and synthesize a novel tolane-core thiol–ene-tailed liquid crystal monomer. Benefitting from the conjugated and extended tolane π-system of the mesogenic core and length extension of the terminal aliphatic tails, the normal-to-plane thermal conductivity value and the thermal conductivity anisotropy value of the corresponding cross-linked main-chain end-on liquid crystal polymer (xMELCP) film reach 3.56 W m −1 K −1 and 15.0, respectively. Compared with the data of a previously reported ester-type thiol–ene xMELCP film, the two primary values of this novel tolane-type thiol–ene xMELCP material are increased dramatically by 46% and 29%, respectively.